2020
DOI: 10.1002/er.5234
|View full text |Cite
|
Sign up to set email alerts
|

Hausmannite Mn 3 O 4 as a positive active electrode material for rechargeable aqueous Mn‐oxide/Zn batteries

Abstract: Batteries with manganese (di)oxide/zinc chemistry and aqueous-based electrolytes have the potential to address energy storage demands of stationary applications primarily because of the abundant availability of Zn and Mn-oxides, their intrinsic low cost, and the high specific/volumetric charge capacities. Herein, we report the use of Mn 3 O 4 (hausmannite phase of manganese oxide) as the positive electrode material in a rechargeable near-neutral Mn-oxide/Zn battery configuration. Electrochemical investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…High yield Mn 3 O 4 NPs are produced by this single step microplasma array method without any pre/post treatments, which requires huge time and energy and toxic chemicals 38 . Stoševski et al 44 reported Hausmannite Mn 3 O 4 NPs as a potential electrode material for rechargeable batteries from their electrochemical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…High yield Mn 3 O 4 NPs are produced by this single step microplasma array method without any pre/post treatments, which requires huge time and energy and toxic chemicals 38 . Stoševski et al 44 reported Hausmannite Mn 3 O 4 NPs as a potential electrode material for rechargeable batteries from their electrochemical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to the difference of methodology, the modifying strategies can be summarized into the following five different categories: interlayer intercalation (e.g., cationic intercalated materials, H 2 O intercalated materials, ions and H 2 O co-intercalated materials, and conducting polymer intercalated materials), doping effect, defect engineering, surface coating (e.g., carbon, metal oxide, and conductive polymer), composite formation, as well as the special morphology control (e.g., nanosphere, nanotube, nanofiber, nanosheets, etc.). [158][159][160][161]…”
Section: Structural Engineering For Cathode Materialsmentioning
confidence: 99%
“…Considering these factors, researchers would like to choose aqueous zinc-ion battery (AZIBs), which has the advantages of high abundance, good safety, good flammability resistance and high ionic conductivity. [4][5][6][7][8][9] Nowadays, many cathode materials are being explored, such as manganese oxides, Prussian blue analogs, and vanadium-based compounds. [9][10][11][12][13] Among these potential cathode materials, the layered structure of vanadium oxide has attracted attention as one of the most promising cathode materials in AZIBs owing to vanadium oxide with a larger interlayer spacing for the high charge-radius ratio of Zn 2+ insertion.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Nowadays, many cathode materials are being explored, such as manganese oxides, Prussian blue analogs, and vanadium-based compounds. [9][10][11][12][13] Among these potential cathode materials, the layered structure of vanadium oxide has attracted attention as one of the most promising cathode materials in AZIBs owing to vanadium oxide with a larger interlayer spacing for the high charge-radius ratio of Zn 2+ insertion. 14 During the electrode preparation process, the polymer binders, such as polyvinylidene fluoride (PVDF) are usually used to attach active materials and conductive agents to the current collector.…”
Section: Introductionmentioning
confidence: 99%